Bibliometric Analysis of Public Administration Research - Judijanto, Loso (Westscience Press, 2025)
This study presents a comprehensive bibliometric analysis of public administration research using data retrieved from the Scopus database and visualized through VOSviewer. The objective is to map the intellectual structure, thematic evolution, and global collaboration patterns in the field from 2000 to 2024. The analysis includes co-authorship, keyword co-occurrence, temporal overlay, and density visualizations to identify the most influential authors, institutions, countries, and research topics. The findings reveal that while traditional themes such as bureaucracy, public policy, and administrative reform remain central, there has been a notable shift toward contemporary topics such as e-government, digital transformation, artificial intelligence, and sustainability. The United States emerges as the leading contributor in terms of publication volume and collaborative influence. The study offers practical insights for researchers, policymakers, and academic institutions, while also contributing theoretically by highlighting the evolution and diversification of public administration as a multidisciplinary field. Despite limitations related to database scope and keyword standardization, this research provides a valuable foundation for guiding future studies and strengthening strategic collaboration in the discipline.